Open access in Kyrgyzstan: Current developments and future directions - BEKBALAEVA, Jyldyz (Institutional Knowledge at Singapore Management University, 2021)
Covered the developments in open access in Kyrgyzstan, including the level of awareness of OA, OER and Creative Commons licenses. Introduced the repositories, KyrlibNet Open Archive and their OA journals on DOAJ.